Duality of tax inflation and its impact on emissions - Ernazarov Nuriddin (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
Economic duality, characterized by the coexistence of different modes of production, consumption, labor markets, taxation, and monetary circulation within the same economy, can significantly impact economic development. In transition economies, duality often leads to underdevelopment, resource mismanagement, and corruption. This research explores the duality of tax inflation and its impact on emissions within such economies, with a focus on the case of Uzbekistan. The study aims to examine how dual monetary systems and tax inflation contribute to economic imbalance and environmental degradation. Utilizing a mixed-methods approach, including qualitative analysis of economic policies and quantitative assessment of emission data, the research reveals that dual monetary systems lead to tax evasion and inefficient resource allocation. The findings highlight the need for integrated economic reforms, emphasizing the unification of monetary circulation and the decentralization of financial decision-making. The implications suggest that addressing fiscal imbalances through optimized tax policies is crucial for sustainable economic development and environmental preservation.